Cohort profile: the Norwegian Registry of Persons Assessed for Cognitive Symptoms (NorCog) – a national research and quality registry with a biomaterial collection. Issue 9 (8th September 2022) - Medbøen, Ingrid Tøndel; Persson, Karin; Nåvik, Marit; Totland, Torunn Holm; Bergh, Sverre; Treviño, Cathrine Selnes; Ulstein, Ingun; Engedal, Knut; Knapskog, Anne-Brita; Brækhus, Anne; Øksengård, Anne Rita; Horndalsveen, Peter Otto; et al.
Abstract : Purpose: The Norwegian Registry of Persons Assessed for Cognitive Symptoms (NorCog) was established to harmonise and improve the quality of diagnostic practice across clinics assessing persons with cognitive symptoms in Norwegian specialist healthcare units and to establish a large research cohort with extensive clinical data. Participants: The registry recruits patients who are referred for assessment of cognitive symptoms and suspected dementia at outpatient clinics in Norwegian specialist healthcare units. In total, 18 120 patients have been included in NorCog during the period of 2009–2021. The average age at inclusion was 73.7 years. About half of the patients (46%) were diagnosed with dementia at the baseline assessment, 35% with mild cognitive impairment and 13% with no or subjective cognitive impairment; 7% received other specified diagnoses such as mood disorders. Findings to date: All patients have a detailed baseline characterisation involving lifestyle and demographic variables; activities of daily living; caregiver situation; medical history; medication; psychiatric, physical and neurological examinations; neurocognitive testing; blood laboratory work-up; and structural or functional brain imaging. Diagnoses are set according to standardised diagnostic criteria. The research biobank stores DNA and blood samples from 4000 patients as well as cerebrospinal fluid from 800 patients. Data from NorCog have been used in a wide range of research projects evaluating and validating dementia-related assessment tools, and identifying patient characteristics, symptoms, functioning and needs, as well as caregiver burden and requirement of available resources. Future plans: The finish date of NorCog was originally in 2029. In 2021, the registry's legal basis was reformalised and NorCog got approval to collect and keep data for as long as is necessary to achieve the purpose of the registry. In 2022, the registry underwent major changes. Paper-based data collection was replaced with digital registration, and the number of variables collected was reduced. Future plans involve expanding the registry to include patients from primary care centres.